Kaposi’s sarcoma in patients with acquired immunodeficiency syndrome (AIDS) – our own observation - Gładysz, Andrzej; Knysz, Brygida; Szybejko-Machaj, Grażyna; Simon, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2000)
Kaposi’s sarcoma is the most common neoplasm observed in patients with AIDS. There is epidemiological and molecular evidence that infection with KSHV is predicted infectious cause of KS; moreover many cytokines and viruses, including HIV, are the cofactors required for the development of AIDS-KS. The clinical picture and course of AIDS-KS varies and is unpredictable, with different response to therapy. In this article authors describe the own clinical experiences in therapy of AIDS-KS, and the reasons of therapeutical failure.